Performance analysis of patch antenna for underwater wireless communication in seawater - Siti Harliza Mohd Razali; Razali Ngah; Yoshihide Yamada; Kamilia Kamardin (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Underwater wireless communication in seawater is becoming more interesting and challenging in recent years. The development of antenna for underwater wireless communication in seawater at 900 MHz UHF range frequency is implemented by using patch antenna. In this paper, the antennas were designed using FEKO, an electromagnetic simulation software, and a suitable size for rectangular patch antenna for seawater application was developed to study the relevance between λ0 with W and L in seawater. The difference between the patches in free space and seawater was the L size, which was slightly bigger, about 0.9 mm, than free space size. But the gain for patch antenna in seawater was found at -2.51 dBi, lower than patch antenna in free space, which was 5.76 dBi due to the path loss in seawater. This shows that attenuation happened, and a better antenna will be design. The one that has better gain, which is around above 2 dBi in seawater, in order to get better performance antenna in seawater environment.